The Association Between Psychosocial Factors and Decision Making Regarding Primary Treatment in Older Women With Early‐Stage Breast Cancer - Gina, Hindler; I, Alabaster; Ross Azura, Zahit; Ali, Jahan; Dana, Giza; Holly M, Holmes; Holly, Blake; Kwok Leung, Cheung; Ruth M, Parks (John Wiley & Sons, InC., 2025)
Background: Breast cancer is increasingly prevalent among older adults, who are likely to have numerous comorbidities and unique psychosocial challenges. Aims: The aim of this study was to measure the prevalence of psychosocial factors in a cohort of older women diagnosed with early‐stage operable breast cancer and the influence these factors may have on treatment decisions. Methods: As part of a prospective study in three UK centres, 199 patients with a new diagnosis of early‐stage operable primary breast cancer, aged ≥ 70 years (mean 77, range 68–93) were recruited. A cancer‐specific Comprehensive Geriatric Assessment (CGA) was conducted within 6 weeks of diagnosis. Association between treatment decision and psychosocial aspects (as measured by the ‘psychosocial support’, ‘social activity’ and ‘social support’ domains) of the CGA was determined. Treatment decision was not guided by this study and was determined usual conventional methods as per the breast multi‐disciplinary team. Results: Scores for ‘psychosocial support’ averaged 82.1/102, ‘social activity’ averaged 13.5/24, and ‘social support’ averaged 43.3/72; with a higher score indicating a more positive outcome. There was no association between total scores in these domains and the type of treatment received. A lower score in three individual questions was associated with a higher likelihood of nonsurgical treatment. Conclusions: While no direct link emerged between overall psychosocial scores and treatment decisions using CGA, specific sub‐questions displayed associations with non‐surgical treatment. This study is the only one of its kind to our knowledge. This may have implications for the design of a pre‐CGA screening tool.